“Aging Means to Me… That I Feel Lonely More Often”? An Experimental Study on the Effects of Age Simulation Regarding Views on Aging - Schmidt, Laura I.; Schlomann, Anna; Gerhardy, Thomas; Wahl, Hans-Werner (Frontiers in Psychology, 2022)
Over the last decades, educational programs involving age simulation suits (ASS) emerged with the ambition to further the understanding of age-related loss experiences, enhance empathy and reduce negative attitudes toward older adults in healthcare settings and in younger age groups at large. However, the impact of such “instant aging” interventions on individuals’ personal views on aging have not been studied yet. The aim of the current study is to address possible effects of ASS interventions on multiple outcomes related to views on aging, i.e., aging-related cognitions (i.e., expectations regarding social losses), awareness of age-related change (AARC) and age stereotypes. Moreover, we explore effects on broader constructs with relevance to aging, i.e., perceived obsolescence, risk perceptions, as well as desired support through technology. In a within-subjects design, N=40 participants (M=61.4 years, SD=6.16) went through a series of established geriatric assessments (i.e., Timed up and Go) with and without an ASS. Views on aging constructs were assessed in standardized questionnaires before and after the ASS intervention. Changes in aging-related cognitions were observed, with more negative expectations regarding social integration and continuous development after wearing the ASS. AARC and age stereotypes did not change from pre- to post-assessment, but participants reported an increased susceptibility to age-associated impairments and stronger feelings of obsolescence. Those participants who exhibited higher difficulties in geriatric assessments while wearing the suit reported higher openness to be supported by intelligent assistive devices or robots afterwards. We conclude that ASS interventions should only be combined with education on losses and gains during the aging process to prevent negative effects on individual views on aging. On the other hand, potentials regarding technology acceptance and formation of intentions to engage in prevention and health behaviors among middle-aged to young-old adults are discussed.